Chondro-Osseous Respiratory Epithelial Adenomatoid Hamartoma (COREAH): Case Report and Literature Review - Andrew Daniel; Eugene Wong; Joyce Ho; Narinder Singh (Case Reports in Otolaryngology)
Chondro-osseous respiratory epithelial adenomatoid hamartoma (COREAH) is an extremely rare lesion of the nasal cavity with only 11 reported cases in the literature. COREAH is of interest as it may be easily mistaken for other diseases of the nasal cavity with higher morbidity, which require significantly different management strategies. We report, to the best of our knowledge, the oldest documented case of COREAH in the literature: an 83-year-old female who presented with headaches and was found to have a posterior nasal septal lesion. Uniquely, the patient had sequential scans performed 1 year apart demonstrating only minor interval growth. We describe our experience in managing a patient with COREAH and review the world literature, to better define aspects of the history, presentation, and investigations that may allow differentiation from more sinister disease.